Pengembangan Strategi Bisnis Pada UMKM Distro Penny Royaltea - Setiawan, Rizky Kurnia; Wijaya, Fanji; Karamang, Ezra; Rahmi, Palupi Permata (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are a form of entrepreneurial activity that plays a vital role in economic development. The contribution of MSMEs to GDP is substantial and increases employment opportunities so that it can reduce the unemployment rate. Penny Royaltea is an MSME engaged in the fashion sector. This study aims to determine the most appropriate SWOT analysis strategy for the Penny Royaltea distro facing business competition. This purpose is to determine the SWOT analysis strategy of Penny Royaltea, to evaluate the MSME Penny Royaltea distro by analyzing Strengths, Weaknesses, Opportunities, and Threats, and to determine the right business strategy for developing the MSME Penny Royaltea distro business in Bandung City. This article aims to determine the internal and external conditions of the business and formulate business development strategies, especially for Penny Royaltea. The results show several strategies that Penny Royaltea can apply, such as conducting product research and innovation, Maximizing the use of technology for online promotion, Emphasizing point of differentiation (PoD) and unique selling points, and providing attractive offline marketing and offers. The results of this study provide managerial implications for Penny Royaltea in developing its business